Particularites Diagnostiques Et Pronostiques De La Dissection Aortique Au Cnhu-Hkm De Cotonou, Benin : A Propos De 6 Cas En 2017 - Adjagba Philippe Mahouna; Bognon Rosaire; Sonou Arnaud; Hounkponou Murielle; Djoh Ingrid; Assani Moutaïrou Salimatou; Yessoufou Tchabi; Houénassi Martin Dèdonougbo (European Scientific Journal, ESJ, 2018)
Aortic dissection (DA) defined by longitudinal cleavage of the aortic wall, at the level of the media from an intimal breach, is a diagnostic and therapeutic emergency. Out of a total of 467 hospitalized patients, we reported 6 cases of aortic dissection (DA) observed at CNHU-HKM, Cotonou, in 2017. The patients were 53.33 years old (33-65 years old), and they comprised of 4 women and 2 men. Hypertension was present in 5 patients. Chest pain, the most common telltale sign, was found in 5 patients but typical only in 2 cases. Three (3) patients had severe hypertension when they were admitted, and 2 had a differential arterial pressure of at least 20 mmHg between the arms. The breath of aortic insufficiency was present in 4 patients. Chest X-ray has contributed to the diagnosis in the 4 cases where it was prescribed. Cardiac Döppler ultrasonography was perfomed in 5 patients, while the ECG gave no contribution to the diagnosis. The diagnostic confirmation was made by the aortic CT scan in all patients and the AD was type A in 5 cases and type B in 1 case according to the Stanford classification. All patients received medical treatment and only 1 patient received both medical treatment and surgery. The outcome was fatal in 5 patients: death of the patient with type B dissection and 4 deaths out of 5 for type A.